THE EFFECT OF CLARITY OF INFORMATION AND COMFORT OF WAITING ROOM ON SATISFACTION WITH DRUG SERVICE THROUGH PERCEPTION OF WAITING TIME - Fadhilah, Anita; Azzuhri, Misbahuddin; Andarini, Sri (Universitas Brawijaya, Indonesia, 2018)
This study was aimed to examine the influence of clarity of waiting time information and the comfort of waiting room towardssatisfaction through waiting time perception of drug services. Chosen observational analytical study by cross-sectional study was used as methods in this study. Sampling technique used in this study was purposive sampling. 120 respondents were chosen as study sample among all of the outpatients out of pocket which waiting for drug services on March - April 2017. Path analysis was used as data analysis method. Study result showed that clarity of waiting time information and the comfort of waiting room had a positive and significant influence on waiting time perception and satisfaction awaiting drug services. As of intervening variable, waiting time perception was contributed increasing influence clarity of waiting time information and the comfort of waiting room towardssatisfaction with drug services. The most predominant variable in constructing satisfaction with drug servicesthrough waiting time perception was the comfort of the waiting room.